Perencanaan Manajemen Sumber Daya Manusia Dan Keuangan Pada Aplikasi Jasa Titip Barang Titip.In - Rois, Mohamad; Syah, Tantri Yanuar Rahmat; Negoro, Dimas Angga; Suwarto, Suwarto (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This activity aims to analyze the human resource management planning process implemented to support the operational of the "Titip.In" goods consignment service application. The "Titip.in" goods consignment service application was developed as a solution to overcome the challenges in the consignment service industry in Indonesia which is still developing. Currently, the consignment service market in Indonesia is dominated by individuals who run informal businesses through social media such as Instagram, WhatsApp, and Facebook. The method is by conducting workshops and training, management consultation assistance and creating modules or practical guides in Titip-in business planning. Good HR planning will be able to manage the business and carry out the company's operational activities and reliable HR will be able to compete globally. Financial planning is useful for predicting business feasibility by showing positive indicators of Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) which are attractive to investors.